CLINICAL STUDY TO COMPARE THE EFFICACY OF NASYA KARMA WITH SHADBINDU TAILA AND ANU TAILA IN MIGRAINE VIS-O-VIS ARDHAVABHEDAKA (AYUSHDHARA, 2020)
Migraine is one of the Ardhavabhedaka roga in which there is vitiation of Vata & Kapha dosha. Currently, conventional medicine has no effective treatment for Ardhavabhedaka. Because of the facts, particularly considering the side effects in the existing methods of treatment, there is the need to develop a treatment protocol. Vairechanika Nasya is the line of treatment as per Acharya Sharangadhara. Therefore, Nasya has been selected as a treatment modality for the present study. "Nasa hi siraso dwaram tena taddapyahanthi tana". The nose is the gateway of the head; hence it acts as an inlet for the Nasya Karma. It destroys the disease of the head. Patients of group A were treated with Shadbindu Taila Nasya for 7 days & patients of group B were treated with Anu Taila Nasya for 7 days. The dose of Nasya is 6 Bindu. The percentage success rate of Group is 57.5% & Group-B is 56.8%. There is no significant difference among the results of the treatment of Group-A and Group-B by paired proportion test of significance for i.e. p